Possible replacement of ZnO treatment in the case of weaning piglets - Albert, Fruzsina; Bodnár, Ákos; Pajor, Ferenc; Póti, Péter; Abayné Hamar, Enikő; Kovács-Weber, Mária; Posta, Katalin; Juhász, Ákos; Mayer, Zoltán; Hidas, András; Fazekas, Natasa; Egerszegi, István (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
The weaning of piglets is a stressful situation which can cause diarrhea, and can lead to very high economic losses. As a solution, Zinc oxide is used for preventive manner, but it is difficult to determine the right amount of it, so the use of high dosage is a general practice. This, in turn, has a detrimental effect on the environment.For a long time, the use of high-dose ZnO has been one of the options to treat diarrhea-induced problems in weaned piglets (http1). However, with its large, excessive use, we have managed to cross a border that can no longer be maintained in the long run from an environmental point of view (http2). As a result, according to Article 35 of Directive 2001/82/EC (EMEA/V/A/118) presented by the CVMP (http3), the European Commission ordered an EU-wide ban on the use of ZnO in the case of pig feeding by 2022 (http4). To solve the existing problem further research is needed now.Along with the limited use or banning of antimicrobials, we need to find new solutions to improve and protect the health of farm animals and maintain their performance. Recently, animal husbandry has been flooded with the use of alternative production-enhancing products that have similar effects to pharmaceuticals (Kamel, 2000).Essential oils, organic acids, enzymes, probiotics (lactobacilli), prebiotics (oligosaccharides) and herbs could be used as feed additives.
Keywords: swine; weaning piglet; ZnO; zink-oxide replacement; swine feeding